Hepatitis B virus persistence after recovery from acute viral hepatitis. - Michalak, T I (1994)
Contrary to current opinion, the disappearance of hepatitis B surface antigen (HBsAg) from the serum, the development of anti-HBs antibodies, and normalization of liver function may not reflect complete virological recovery from acute hepatitis B virus (HBV) infection. By using the polymerase chain reaction (PCR), in the current study we demonstrate long-term persistence of HBV DNA in the serum and peripheral blood mononuclear cells (PBMC) of four patients for up to 70 mo after complete clinical, biochemical, and serological recovery from acute viral hepatitis. Serum HBV DNA reactivity co-sedimented with HBsAg in sucrose gradients, and it displayed the size and density characteristics of naked core particles and intact HBV virions, presumably contained within circulating immune complexes in these anti-HBs antibody-positive sera. HBV DNA was also present in PBMC in late convalescent samples from all four patients, and HBV RNA was detected in late convalescent phase PBMC in two of these patients. These results suggest that HBV DNA, and possibly HBV virions, can be present in the serum, and that the viral genome can persist in a transcriptionally active form in PBMC for > 5 yr after complete clinical and serological recovery from acute viral hepatitis.